Franchising, Validation, and Branch Campuses in the European Union - Bischof, Lukas (International Higher Education, 2014)
European Higher Education is growing together. Both students and institutions are increasingly going abroad to obtain or offer education. Lately, the issue of branch campuses, franchising or validation arrangements have caused controversy. While European law guarantees all EU universities to offer their study programs in other EU Member States, there is not yet an overarching form of cross-border quality assurance. A recent study has investigated the prevalence of cross-border provision of higher education as well as its regulation in 27 Member States of the European Union. This article explores existing loopholes and makes recommendations for a European quality assurance framework for cross-border education.